The relationship between tradition, flexibility, agility, and football playing skills - Rahmad Hidayat; Dedi Saputra (Pelita International Publishing, 2024)
Psychological and physiological factors influence the ability to play Football. Physiological factors are physical conditions, flexibility, and agility, while psychology has aspects of tradition. This study aims to determine the contribution of tradition, flexibility, and agility to the ability to play Football at Putra Banna Football School, Kutablang, Bireuen Regency, Aceh, Indonesia. The population in this study was all 33 students. Based on the sampling reference with the total sample method, all students were sampled. From the data analysis, it can be obtained that there is a correlation between tradition, flexibility, and agility with the ability to play football.